Germany’s dependence debate: a systematic analysis of the impact of Russian natural gas import dependence - Stoelzel Chadwick, Christina Marilla (Kansas State University, 2021)
This dissertation analyzes the impact of increasing natural gas import dependence on the foreign policy behavior of Western European countries, and specifically Germany, utilizing both quantitative and qualitative methods. I argue that the influence of an “energy weapon” should be assessed in the context of the conditions for its effective application. The question is, in other words, whether a higher level of import dependence in energy leads to the alignment of the foreign policy of the dependent state with the energy supplying state. I propose that a greater Russian natural gas import dependence leads to a greater degree of foreign policy alignment or Affinity of the energy import dependent state with the exporting state. The quantitative analysis examines the impact of natural gas dependence on the foreign policy alignment of nineteen natural gas importers from 1995 to 2013 and, more specifically, Germany, with the Soviet Union and, subsequently, the Russian Federation from 1979 to 2012. The data from the time-series cross-sectional analysis and the time-series analysis of Germany corroborates that a higher level of Russian natural gas import dependence leads to a greater foreign policy alignment of the import dependent state with the Russian Federation. The qualitative analysis uses four case studies to examine the position of German chancellors toward the Soviet Union and the Russian Federation as well as Russian natural gas imports and how it changed as imports increased. The case studies include the NATO pipeline embargo of November 1962, the first natural gas agreement, the construction of the Urengoy-Uzghorod pipeline in the early 1980s and U.S. sanctions against it, and the agreement to build Nord Stream in 2005. I conclude that the “energy weapon” has a systemic impact on the foreign policy of the import dependent state by inducing foreign policy alignment and deterring foreign policy decisions that might alienate the Russian Federation. The “energy weapon” not only affects the foreign policy of states directly affected by a supply disruption or threat thereof but has an impact on the foreign policy position of natural gas import dependent states toward the Russian Federation in general.
Keywords: Natural gas; Import dependence; Russia; Germany; Energy dependence